Development of Eco-STEM Based E-Worksheet to Improve Junior High School Students Scientific Creativity - Iwan Wicaksono; Amalia Melinda; Mazlina Musa (Jurnal Pendidikan Sains Indonesia, 2026)
This research aims to develop and determine the validity, practicality, and effectiveness of Eco-STEM based E- worksheet to improve scientific creativity among junior high school students in the subject of substances and their changes. The background of this research is based on the lack of interactive, contextual teaching materials and the lack of learning that emphasizes scientific creativity and environmental issues. In addition, there is also a lack of utilization of digital media in learning. This research uses the ADDIE development model. The research subjects were 26 students in class VII A MTsN 2 Jember in the odd semester of the 2025/2026 academic year. Its validity was classified as very high based on expert evaluations of content accuracy, language clarity, presentation quality, and graphical design in alignment with the curriculum. The practicality results indicated an average score of 94% (very practical category), demonstrating that the E-worksheet can be implemented smoothly and consistently with the planned learning activities. Its effectiveness in improving students’ scientific creativity was reflected in the average N-gain value of 0.60 (moderate category), indicating meaningful improvement in students’ scientific creativity abilities. In addition, students’ responses yielded an average score of 92.1% (excellent category), highlighting positive perceptions of the E-Worksheet in terms of visual appeal, ease of use, and overall usefulness. In conclusion, Eco-STEM based e-worksheet is suitable for use as an innovative teaching material to improve students' scientific creativity